Endogenous trans-translation structure visualizes the decoding of the first tmRNA alanine codon - Teran, David; Zhang, Ying; Korostelev, Andrei A. (Frontiers in Microbiology, 2024)
Ribosomes stall on truncated or otherwise damaged mRNAs. Bacteria rely on ribosome rescue mechanisms to replenish the pool of ribosomes available for translation. Transtranslation, the main ribosome-rescue pathway, uses a circular hybrid transfer-messenger RNA (tmRNA) to restart translation and label the resulting peptide for degradation.Previous studies have visualized how tmRNA and its helper protein SmpB interact with the stalled ribosome to establish a new open reading frame. As tmRNA presents the first alanine codon via a non-canonical mRNA path in the ribosome, the incoming alanyl-tRNA must rearrange the tmRNA molecule to read the codon. Here, we describe cryo-EM analyses of an endogenous Escherichia coli ribosome-tmRNA complex with tRNA Ala accommodated in the A site. The flexible adenosine-rich tmRNA linker, which connects the mRNA-like domain with the codon, is stabilized by the minor groove of the canonically positioned anticodon stem of tRNA Ala . This ribosome complex can also accommodate a tRNA near the E (exit) site, bringing insights into the translocation and dissociation of the tRNA that decoded the defective mRNA prior to tmRNA binding. Together, these structures uncover a key step of ribosome rescue, in which the ribosome starts translating the tmRNA reading frame. ** from Frealign (FSC_part) * from Phenix § root mean square deviations from ideal values # RNA backbone suites as defined by Molprobity